Effect of Rupiah Exchange Rate, GDP Growth, and Dow Jones Index on Composite Stock Price Index in Indonesia Stock Exchange - Safitri Oktavia; Wiwik Handayani (JASF: Journal of Accounting and Strategic Finance, 2018)
The capital market is a meeting place for stock sellers and buyers with the aim of getting maximum profits. To get these benefits, investors need information about the stock price index. Factors that influence the Stock Price Index are important information for investors. The composite stock price index (CSPI) is one of the main indicators that reflects the performance of the capital market whether it is experiencing an increase or is experiencing a decline. These factors include the rupiah exchange rate, GDP growth, and the Dow Jones index. This study aims to prove and analyse the effect of the rupiah exchange rate, GDP growth, and the Dow Jones index Average (DJIA) on the composite stock price index on the Indonesia stock exchange for the period 2012-2015. The population and sample of this study are forty-eight CSPI data from the Indonesia Stock Exchange. Data is collected by means of documentation and then analysed. The data analysis technique used in this study is multiple linear regression analysis techniques. Based on the results of the analysis it is known that the rupiah exchange rate has no effect on the Composite Stock Price Index (CSPI). While GDP growth and the Dow Jones index Average (DJIA) have affected the Composite Stock Price Index (CSPI). For further research, it is considered necessary to review other factors that can influence the movement of the stock price index, for example, the company's fundamental factors such as profit, loss, financial ratios, and others.